Midazolam: Effects on psychomotor performance and subjective aspects of sleep and sedation in normal volunteers - Gudgeon, A. C. (1983)
1 Twelve healthy volunteers each received acute doses of placebo and .5, 10, 15 and 20 mg of midazolam. Seven subjects were tested before and 1, 4 and 7 h after treatment. Five subjects were given the same five treatments nocturnally and tested the following morning, 10-12 h after treatment. 2 Tests on various measures of sedation (choice reaction time and critical flicker fusion) and of drowsiness (line analogue rating scales) showed midazolam at 15 and 20 mg dose levels to be a potent sedative agent. 3 The present results suggest that the activity of midazolam is at a maximum 1 h after ingestion and that the effects of the drug have dissipated 7 h after treatment.